2008
DOI: 10.2215/cjn.03740907
|View full text |Cite
|
Sign up to set email alerts
|

Smoking

Abstract: Although it is beyond any doubt that smoking is the number one preventable cause of death in most countries, smoking as an independent progression factor in renal disease has been questioned against the background of evidence-based criteria. This is because information from large, randomized, prospective studies that investigate the effects of smoking on renal function in healthy individuals as well as in patients with primary or secondary renal disease are lacking. Since 2003, a substantial number of clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
180
1
28

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(214 citation statements)
references
References 131 publications
(124 reference statements)
5
180
1
28
Order By: Relevance
“…Regarding lifestyle habits, there was a higher percentage of smokers in the group without chronic kidney disease, which was significant (p<0.05) for currently active smokers and was almost significant with regards to those who were former smokers. This finding differs from those of several other studies that have shown an association between smoking and the development and progression of chronic kidney disease (19)(20)(21) . However, the retrospective nature of the present study and the data gathered from patient charts did not allow for the assessment of data relevant to this habit such as time of abstinence among those who reported being former smokers.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding lifestyle habits, there was a higher percentage of smokers in the group without chronic kidney disease, which was significant (p<0.05) for currently active smokers and was almost significant with regards to those who were former smokers. This finding differs from those of several other studies that have shown an association between smoking and the development and progression of chronic kidney disease (19)(20)(21) . However, the retrospective nature of the present study and the data gathered from patient charts did not allow for the assessment of data relevant to this habit such as time of abstinence among those who reported being former smokers.…”
Section: Discussioncontrasting
confidence: 99%
“…Rapid growth in puberty often unmasks renal dysfunction 78 because abnormal kidneys may be unable to accommodate the demands of increased growth. It is also important that adolescent patients, particularly those nearing transition to adult practitioners, be aware of their history of prematurity, understand their increased long-term risk for CKD, and receive counseling regarding modifiable risk factors for CKD progression (such as smoking, 79 hypertension, 80 or obesity 81 ).…”
Section: Figurementioning
confidence: 99%
“…Obesity and a central fat distribution pattern are associated with renal impairment 8) . Furthermore, previous reports have demonstrated that unhealthy lifestyle habits such as smoking [9][10][11][12] , heavy alcohol consumption 13) , and an unhealthy diet (ingesting high amounts of animal fat 14,15) , salt 7,16) , and soft drinks 17,18) ) can lead to the development of proteinuria/albuminuria or CKD. However, another study reported that smoking was associated with an increased glomerular filtration rate (GFR) 19) ; thus, the effects of unhealthy lifestyle factors on CKD patients is unclear, and few reports have investigated the relationships between lifestyle habits and proteinuria or eGFR.…”
Section: Introductionmentioning
confidence: 99%